Udział plotki i plotkowania w komunikacji ustnej na przykładzie komunikacji biurowej – podejście hybrydowe: pragma-, socjo-, psycho- oraz ekolingwistyczne - Kaus, Jerzy; Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2021)
The article aims at analysing the concept of gossip at workplace. The main goal of the article is to answer such questions as: what is gossip? Who is involved in spreading gossip at workplace? What are the sources of gossips? The first part (section 1) of the article is theoretical and aims at defining the concept of gossip. The second part (sections 2 and 3) analyses the results of a questionnaire which was carried out among forty respondents. The results are compared with the theoretical assumptions put forth by a number of research works discussed briefly in the article.